Gastronomic experience and consumer behavior: Analyzing the influence on destination image - Kovalenko, A.; Dias, Á.; Pereira, L.; Simões, A. (Foods, 2023)
Gastronomy experiences are becoming a fundamental factor that influences the making of a decision regarding choosing a travel destination, as well as being a crucial factor in shaping tourists’ satisfaction regarding their overall travel experience. The aim of the study is to identify and explain the simultaneous impact of the key factors that influence a gastronomic experience and their impact on tourists’ satisfaction with a trip and the destination’s brand. These issues were addressed within the context of Ukraine, as this is an overlooked area of academic research, and an online survey was conducted, targeting domestic and international tourists. Structural equation modeling was used to assess and reveal the proposed hypotheses in the model. The study contributed to the theoretical understanding of the key factors that increases the occurrence of a memorable gastronomic experience and the relationship between the experience of food and its role in the satisfaction of and the perceived brand of a destination. Moreover, the finding showed that past experience and prior knowledge have a positive influence on the gastronomy experience, while tourists’ prior knowledge effects the perceived quality of a destination’s cuisine, as well as the food activities in the destination. Linkages in the model were empirically supported by statistical analyses. Nonetheless, the various level of the tourists’ involvement with gastronomy might be used as an input to examine and improve the memorable gastronomic experience on-site. The research simultaneously highlighted the importance of gastronomy to tourist destinations for positioning on international and domestic markets. The paper not only provides theoretical but also practical implications. The hospitality and tourism businesses benefit from acknowledging the importance of local food and the local food market. The findings of this study are also deemed to assist destination marketers who observe that tourists have become more demanding in search of unique experiences offered by destinations.